(untitled) (Global Journal of Science Frontier Research, 2017)
The newly identified albino mutation, w*-5200, arose in a maize (Zea mays) population derived from Robertson’s Mutator transposon tagging crosses (Cook, 1988). Due to municipal water restrictions lasting three growing seasons, classical genetic allelism testing was not practical. Instead a molecular approach was pursued in an attempt to verify the genetic locus causing the mutant phenotype. Sequences of w*-5200 and 616B w14-N335 were compared to identify defects that would lead to inactivation of the gene in each, yielding evidence of neither a large-scale insertion nor any other obvious block to gene expression. Ultimately the lifting of water restrictions allowed a traditional allelism test, which verified that the novel mutation affects the w14 locus.